Medical imaging of pulmonary disease in SARS-CoV-2-exposed non-human primates. Issue 2 (February 2022) - Stammes, Marieke A.; Lee, Ji Hyun; Meijer, Lisette; Naninck, Thibaut; Doyle-Meyers, Lara A.; White, Alexander G.; Borish, H. Jacob; Hartman, Amy L.; Alvarez, Xavier; Ganatra, Shashank; Kaushal, Deepak; Bohm, Rudolf P.; et al.
Abstract : Chest X-ray (CXR), computed tomography (CT), and positron emission tomography–computed tomography (PET-CT) are noninvasive imaging techniques widely used in human and veterinary pulmonary research and medicine. These techniques have recently been applied in studies of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-exposed non-human primates (NHPs) to complement virological assessments with meaningful translational readouts of lung disease. Our review of the literature indicates that medical imaging of SARS-CoV-2-exposed NHPs enables high-resolution qualitative and quantitative characterization of disease otherwise clinically invisible and potentially provides user-independent and unbiased evaluation of medical countermeasures (MCMs). However, we also found high variability in image acquisition and analysis protocols among studies. These findings uncover an urgent need to improve standardization and ensure direct comparability across studies. Highlights: In non-human primates (NHPs), characteristic radiographic abnormalities (best observed by high-resolution imaging), combined with concordant immunological, virological, and lung histopathological findings, mirror mild-to-moderate human disease. Noninvasive medical imaging can visualize otherwise 'silent' disease at high resolution and generates quantifiable measurements that are particularly important in sublethal models, providing an essential complement to standard immunological, virological, and pathological assays, which can only be performed as snapshots (not longitudinally) or may be difficult to perform. The incorporation of advanced medical imaging tools in NHP studies for coronavirus disease 2019 (COVID-19) research is not without challenges, including high experimental costs due to the limited availability of equipment in high containment environments, frequency of anesthesia events required for imaging, and the number of animals that can practically be imaged at a single time point.